Metabolic inflexibility in youth with obesity: Is it a feature of obesity or distinctive of youth who are metabolically unhealthy?. Issue 2 (1st December 2021) - Gebara, Nour Y.; Kim, Joon Young; Bacha, Fida; Lee, SoJung; Arslanian, Silva
Summary: Individuals with obesity have metabolic inflexibility with diminished fasting fat oxidation and blunted increase in respiratory quotient (RQ) in insulin‐stimulated states. However, it is unclear if metabolic inflexibility is a characteristic of obesity per se or is unique to youth who have metabolically unhealthy obesity (MUO) compared with metabolically healthy obesity (MHO). We investigated metabolic flexibility in youth with MUO, MHO and normal weight (NW) and compared their metabolic characteristics. Youth ( n  = 188) were divided, based on cut‐off points for in vivo insulin sensitivity (IS) of adolescents with NW, into 137 with MUO and 51 with MHO. Fasting hepatic IS (HIS) from hepatic glucose production by [6, 6‐ 2 H2 ]glucose, adipose tissue IS (ATIS) from whole‐body lipolysis by [ 2 H5 ]glycerol, RQ (indirect calorimetry) during fasting and a hyperinsulinemic (80 mU/m 2 /min)‐euglycemic clamp were measured. Youth with MUO versus MHO had blunted ΔRQ ( p  = .035) and lower HIS and ATIS (both p  < .0001), while ΔRQ, HIS and ATIS were not different between youth with MHO and NW. In a pair‐matched sub‐analyses of 30 MUO and 30 MHO the results were similar to the total cohort. Metabolic inflexibility, does not appear to be a feature of obesity per se rather distinctive of youth with MUO, who also have worse HIS and ATIS compared with youth with MHO.